Proteção da natureza e produção da natureza: política, ideologias e diversidade na criação de unidades de conservação na periferia sul da metrópole belo-horizontina - Ana Carolina Pinheiro Euclydes (2012)
In the southern suburbs of the metropolitan region of Belo Horizonte (Minas Gerais, Brazil), where the urban space meets the iron mines of the Quadrilátero Ferrífero area, a complex of protected areas has been constructed. The study of this complex, hardly recognizable in fieldbut yet largely employed in political speeches and advertising, suggests that the discussion of those protected areas outcomes the biodiversity conservation theme, revealing conflicts on the uses of space, as well as environmental conflicts, related to the threat of wrecking of certainspatial practices. Given this scenario, and considering political, ideological and historical aspects of space, this study seeks to understand the roles desired/played by the protected areas in this regions space production, which is accomplished through literature review, interviews and assessment of speeches held in public meetings set to discuss issues such as mining and environmental protection. Identifying those expectations concerning the protected areas andthe spatial dynamics in which they work, we give elements to the construction of the concept of reserve space production, a process that may be in course in this part of the metropolis. With these thoughts, we expect to contribute to the debates on space production and organization as well as for the ones dedicated to the critics of environmental protectionpolitics and as much as possible to the articulation between those two themes.